Submersible Compressor to Enhance Gas Production at The Gas Field - MUHAMMAD SYUKRI BIN MOKHTAR, MUHAMMAD SYUKRI (Universiti Teknologi Petronas, 2009)
Over the next 20 years, the role of natural gas in global energy consumption will increase. The speed of transition to natural gas will be driven by environmental issue, market demand and latest technology. This project is about developing a technological solution for the oil and gas industry's recognized problem of maximizing gas extraction from the gas field by trialing the technology which will increase production. The objectives of this study are to identify an option to boost the gas production and to maintain the pressure at the base of the well by means to prevent the problem of liquid loading by developing the submersible compressor. Submersible Compressor helps to maintain the well energy to lift the gas to the surface by maintaining the pressure differential between the well and surface. The submersible compressor is used in multiple stage compression modes. Scope of study includes the drawing of full scale submersible compressor by using CATIA & AUTOCAD then exported to GAMBIT and FLUENT for subsequence analysis. The results of the analysis consist of discharge pressure and velocity of the compressor. The main target is to increase the discharge pressure so that the pressure differential between well and surface increased.